Are the results of the RATE-AF trial reproducible in daily practice? Clinical outcomes with digoxin vs beta-blocker for heart rate control in permanent atrial fibrillation. (14th October 2021) - Fauchier, L; Bisson, A; Bodin, A; Spiesser, P.H; Clementy, N; Pierre, B; Babuty, D; Lip, G.Y.H
Abstract: Background: There is little evidence to support selection of heart rate control therapy in patients with permanent atrial fibrillation (AF), in particular those with coexisting heart failure. In the recent RATE-AF trial that included patients with permanent AF and symptoms of heart failure, treatment with low-dose digoxin or bisoprolol did not result in statistically significant difference in quality of life at 6 months. The purpose of the study was to analyse whether the clinical outcomes may differ among unselected patients with permanent AF treated with digoxin or beta-blocker seen in daily practice. Methods: All patients with atrial fibrillation (AF) seen in an academic institution were identified in a database. We examined the clinical course of 8962 consecutive patients with AF seen over a 10-year period. The adverse outcomes were investigated during follow-up and we identified the causes of death. Among them 1, 787 patients had the RATE-AF criteria of inclusion (permanent AF, age ≥60 and NYHA ≥2), of whom 512 patients (29%) were treated with beta-blocker alone, 425 (24%) were treated with digoxin alone and 237 (13%) were treated with both a beta-blocker and digoxin. Outcomes in patients treated with beta-blocker alone or digoxin alone were compared after 1:1 propensity-score matching. Results: After propensity score matching, 270 patients treated with beta-blocker were matched 1:1 with 270 patients treated with digoxin. In these patients (age 79±8 years, CHA2DS2VASc score 4.0±1.3), 125 deaths were recorded during a follow-up of 2.2±2.7 years (median 1.1, interquartile 0.1–3.5 years, yearly rate of death 10.4%) including 72 cardiovascular deaths (yearly rate 6.0%). Major clinical events (all-cause death, myocardial infarction, ischemic stroke or major bleeding) were recorded in 192 patients (yearly rate 19.1%). In this matched analysis, risk was not statistically significant in the 2 groups for all-cause death (HR 0.95, 95% CI 0.67–1.35 for beta-blocker use vs digoxin use), cardiovascular death (HR 1.23, 95% CI 0.77–1.96 for beta-blocker use vs digoxin use) or major clinical events (HR 0.98, 95% CI 0.74–1.31 for beta-blocker use vs digoxin use). Conclusion: Our analysis included more patients and had a longer follow-up than in the RATE-AF trial, resulting in a 10-fold higher number of clinical events. We found that among patients with permanent AF and symptoms of HF, there was no statistically significant difference in the risk of all-cause death, cardiovascular mortality and major clinical events between those treated with digoxin or beta-blocker. Concerns regarding the use of digoxin, such as the narrow therapeutic window and drug interactions, were not issues resulting in worse clinically relevant cardiovascular outcomes with the approach used in the current study. Funding Acknowledgement: Type of funding sources: None.